Analisis Pengaruh Determinasi Intrinsik Determinasi Ekstrinsik dan Kondisi Dinamis Kelompok terhadap Kemandirian Usahatani (Analisis Jalur pada Kelompok Tani Bangkit Merbabu Kabupaten Semarang) - M. Zulfa ‘Ulumuddin Alwy; Heru Setiyadi; Endro Puji Astoko (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Farm independence is a crucial foundation for the sustainability of farmers’ agribusiness, as it enables them to optimize resources and adapt to market changes. A farmer group approach is increasingly relevant for strengthening this independence through collaborative knowledge and shared resources. This study aims to (1) analyze the influence of intrinsic determination and extrinsic determination on the dynamic movement of the group and (2) analyze the influence of intrinsic determination, extrinsic determination, and dynamic movement of the group on the independence of farmers in farming. The study was conducted from January to March 2024 at the Bangkit Merbabu Farmers Group in Batur Village, Getasan Subdistrict, Semarang District, Central Java. A total of 42 farmers were selected by simple random sampling as the research sample. Data were collected using questionnaires that measured the four research variables: the influence of intrinsic determination, extrinsic determination, and the dynamic movement of the group on the independence of farmers in farming. The data were analyzed using path analysis with the assistance of SPSS 21. The path analysis results showed significant contributions of intrinsic determination. Intrinsic determination had a strong direct influence on farm independence, while external factors contributed more through indirect paths mediated by the dynamic movement of the group. The dynamic movement of the group itself also had a positive direct effect on the level of farm independence. These findings suggest that enhancing farmers’ knowledge and skills directly increases their independence, and extrinsic support further strengthens this effect through interactions within the farmer group.